Kandungan Kadar Air dan Kadar Protein pada Bakso Ayam Broiler dengan Putih Telur Sebagai Bahan Pengenyal pada Konsentrasi yang Berbeda - Munassir B, Munassir B; Nurhaeda, Nurhaeda; Irmayani, Irmayani (Fakultas MIPA UNM, 2019)
Abstract. This study aims to determine the effect of egg white at different concentrations on the content of water content and protein content in broiler chicken meatballs. This research uses Completely Randomized Rangcangan (CRD) with three replications and treatment four times, namely T0 = Control, T2 = 15 grams of Egg White, T2 = 30 grams of Egg White, T3 = 75 grams of White Egg. Variety analysis showed the addition of egg whites as pengeyal material at different concentrations significantly affected the content of water content and did not significantly affect the content of protein content. The average water content in the highest to lowest broiler chicken meatballs was obtained from P3 treatment of (61.48%), P0 (58.48%), P1 (53.58%), and P2 (43.32%). The average protein content in the lowest broiler chicken meatballs was obtained from treatment P0 (12.54%), P2 (13.29%), P1 (14.13%), and P3 (15.32%). From the results of research the content of water content and protein content with egg whites as different pengeyal ingredients is 43 grams of egg white. The best water content obtained in P2 treatment with an average value of 43.32%. The best protein content obtained in P3 treatment with an average value of 15.32%.Keywords: broiler, egg white, moisture content, protein content